Tumor-associated lymphatic vessel density is a postoperative prognostic biomarker of hepatobiliary cancers: a systematic review and meta-analysis - Li, Jin; Liang, Yu-Bo; Wang, Qing-Bo; Li, Yu-Kai; Chen, Xing-Ming; Luo, Wan-Ling; Lakang, Yawhan; Yang, Zi-Sheng; Wang, Yan; Li, Zhi-Wei; Ke, Yang (Frontiers in Immunology, 2025)
PurposeThis study aimed to investigate whether tumor-associated lymphatic vessel density (LVD) could predict the survival of patients with hepato-biliary-pancreatic (HBP) cancers after radical resection.MethodsA systematic search was conducted using PubMed, Embase, and Cochrane Library from the inception to July 31, 2024 for literature that reported the role of LVD in overall survival (OS) and recurrence-free survival (RFS) of patients with HBP cancers after radical resection.ResultsTen studies with 761 patients were included for the meta-analysis. The results indicated that a higher level of LVD was associated with worse OS (hazard ratio, HR = 2.87, 95% CI 1.63 to 5.04) and worse RFS (HR = 3.18, 95% CI 1.41 to 7.17) in HBP cancers. Subgroup analysis based on pathological types revealed that a higher level of LVD was significantly related to worse OS in hepatocellular carcinoma (HCC) (HR = 2.35, 95% CI 1.16 to 4.78), cholangiocarcinoma (HR = 4.65, 95% CI 1.70 to 12.70), and gallbladder cancer patients (HR = 4.64, 95% CI 1.37 to 15.71). The levels of LVD were not significantly associated with OS in pancreatic adenocarcinoma patients after radical resection (HR = 1.08, 95% CI 0.61 to 1.89). Similarly, a higher level of LVD was significantly associated with worse RFS in HCC (HR = 1.92, 95% CI 1.01 to 3.65) and cholangiocarcinoma patients (HR = 4.54, 95% CI 2.10 to 9.83).ConclusionsA higher level of LVD was a biomarker for the prediction of worse OS and RFS in patients with hepatobiliary cancers after radical resection.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024571167.